Pemberian Prioritas Bantuan Terhadap Wilayah Potensi Bencana Gempa Bumi Menggunakan Metode Likert dan Weighted Sum Model - Diana Rendrarini; Pradityo Utomo; Dwi Nor Amadi; Candra Budi Susila (Journal of Computer and Information Systems Ampera, 2025)
Earthquakes are one of the natural disasters that frequently occur in several regions of Indonesia. The government can map in advance the areas that are prone to earthquakes. The results of this mapping can serve as a reference for prioritizing aid distribution to regions with high earthquake disaster potential. This study utilizes the Weighted Sum Model (WSM) to map the priority areas for government aid distribution. The WSM method provides an output ranking regions from high priority to low priority. Several criteria are considered, including the number of exposed populations, the number of disabled individuals, the number of impoverished residents, the number of vulnerable age groups, and the class of exposed populations. Since the exposed population class is non-numeric data, this study employs the Likert method to convert it into numeric data. In addition to criteria, this study also utilizes alternative data, specifically the names of sub-districts in Pacitan Regency, East Java. The combination of the Likert and WSM methods helps in recommending regions with earthquake disaster potential as priority aid recipients. The most prioritized region for receiving aid is Tulakan Sub-district, Pacitan Regency, East Java. Based on WSM calculations, Tulakan Sub-district has the highest WSM final score of 26,642.35, making it the top-priority region compared to others.